The Greek Aspect of the Post-War Territorial Settlement in the USSR-USA Relations (1945–1946) - Kalinin, A. A. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2016)
The article discusses the positions of the USSR and the USA as to the territorial national claims of Greece after World War II. The Greek government claimed the Dodecanese Islands in the Aegean Sea, the Island of Sazan in the Adriatic Sea, Northern Epirus (South Albania), and also demanded a rectification of the Greek-Bulgarian border. As a result, only the Dodecanese Islands were ceded to Greece. The author analyzes the discussion on the Greek issue at sessions of the Council of Foreign Ministers and the Paris Peace Conference. The article also considers the Soviet plans to gain a base of trade ships in the Mediterranean Sea. The process of territorial settlement on the Balkan Peninsula is considered in the context of the origins of the Cold War. At the Paris Peace Conference it was the first time that two hostile coalitions of countries led by the USA and the USSR had clashed. Greek territorial claims to northern neighbours led to an aggravation of contradictions between the Balkan states and contributed to the support of the Communist insurgents by Albania, Yugoslavia and Bulgaria during the Greek Civil War of 1946–1949. The analysis is made referring to official American and Soviet diplomatic documents and memoirs, as well as materials from the Foreign Policy Archive of the Russian Federation and the Russian State Archive of Socio-Political History.